Surface-specific visible light luminescence from composite metal oxide nanocrystals - Sternig, Andreas; Bernardi, Johannes; Mckenna, Keith; Diwald, Oliver (Journal of Materials Science, 2015)
Low-coordinated surface elements on metal oxide nanoparticles represent the basis for a new concept of luminescent nanoparticles made of abundant, non-toxic, and thermally stable materials. This combined experimental and theoretical study describes the generation and stability of Ba-doped MgO nanoparticle surfaces and their optical absorption and luminescence dependence on Ba loading. It is demonstrated that the vapor phase growth process employed here represents a particularly robust synthesis approach for particle powders with reproducibly adjustable photoluminescence emission properties in the range between blue and yellow light. Moreover, this in-depth characterization also provides an understanding of the electronic and optical characteristics of this nanoparticulate material with a so far unnoticed potential for solid-state light applications that are based on down conversion of UV ligh